2015
DOI: 10.1016/j.tjog.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of premature serum progesterone rise on embryo transfer outcomes and the role of blastocyst culture and transfer in assisted reproductive technology cycles with premature progesterone rise

Abstract: PPR did not significantly compromise the clinical outcomes in this series. However, shifting to blastocyst transfer probably could increase the live birth in cycles with PPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…20 In our data, there were both cleavage and blastocyst stage embryo transfers, although there are many conflicting results on the impact of embryo stage on implantation in cycles with impaired endometrial receptivity. 21,22 According to our results, clinical pregnancy and implantation rates were similar between groups with the transfer of two different embryo stages. Subgroup analyses showed that only the predictive value of AUCEM remained statistically significant for the cycle outcome in a subgroup of women with blastocyst transfers.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…20 In our data, there were both cleavage and blastocyst stage embryo transfers, although there are many conflicting results on the impact of embryo stage on implantation in cycles with impaired endometrial receptivity. 21,22 According to our results, clinical pregnancy and implantation rates were similar between groups with the transfer of two different embryo stages. Subgroup analyses showed that only the predictive value of AUCEM remained statistically significant for the cycle outcome in a subgroup of women with blastocyst transfers.…”
Section: Discussionsupporting
confidence: 64%
“…In our data, there were both cleavage and blastocyst stage embryo transfers, although there are many conflicting results on the impact of embryo stage on implantation in cycles with impaired endometrial receptivity . According to our results, clinical pregnancy and implantation rates were similar between groups with the transfer of two different embryo stages.…”
Section: Discussionsupporting
confidence: 50%
“…[ 2 14 ] There was no concomitant rise in LH levels on the day of trigger in association with premature progesterone elevation in our study. In the study by Huang et al .,[ 25 ] the incidence of PPR was 13.02%. The incidence of PPR in the GnRH agonist subgroup (18%) was significantly higher than in the GnRH antagonist subgroup (9.31%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PER in our study was 55.5% (142/256), based on a cut-off level of 1.5nmol/L for P 4 . This igure is high if compared with igures of 13.19% [19], 13.02% [18] and 38.3% [7]. However, comparison is dif icult when the de inition of PE is different in various studies.…”
Section: Discussionmentioning
confidence: 82%
“…Lower pregnancy rate and higher pregnancy loss with PE in IVF cycles had been observed in studies conducted by Silverberg, et al [4], although the mechanism of this remains controversial [4,13]. Then, several authors investigated the effect of PE during the IVF cycles with GnRH analogues, some of these reported negative impact on the live birth and pregnancy rate, while others didn't ind any association [14][15][16][17][18]. T he aim of this study was to assess the validity of progesterone level on hCG day (P 4 ) in the prediction of IVF/ ICSI cycles' outcome in a Saudi setting.…”
mentioning
confidence: 99%